Word and Image in Russian History Essays in Honor of Gary Marker - di Salvo, Maria; Kaiser, Daniel H.; Kivelson, Valerie A. (Academic Studies Press, 2015)
''Word and Image'' invokes and honors the scholarly contributions of Gary Marker. Twenty scholars from Russia, the United Kingdom, Italy, Ukraine and the United States examine some of the main themes of Marker's scholarship on Russia-literacy, education, and printing; gender and politics; the importance of visual sources for historical study; and the intersections of religious and political discourse in Imperial Russia. A biography of Marker, a survey of his scholarship, and a list of his publications complete the volume.